Analysis of Marketing Risk Mitigation Strategies in Shedded Tuna Fish Products Using Failure Mode and Effect Analysis (FMEA) and Analytical Hierarchy Process (AHP) Methods (Case Study: UMKM Abon Jaya Mandiri) - Ramadhani, Asliyah Rizki; Utomo, Dhuto Suh; Gunawan, Suwardi (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2025)
UMKM Abon Jaya Mandiri is a small business that processes tuna fish into shredded fish products. The marketed tuna floss products have several advantages, such as being a healthy option for families as they are made without the use of cooking oil and MSG, and they are certified with SNI standards. Despite these strengths, the business faces marketing challenges, including product damage, price competition, an unstrategic sales location, and minimal social media promotion. These challenges result in many products not being sold optimally each month. This study aims to, Identify marketing risks faced by UMKM Abon Jaya Mandiri. Assess and categorize marketing risks using the Failure Mode and Effect Analysis (FMEA) method. Provide risk mitigation strategies that can be implemented by UMKM Abon Jaya Mandiri. The research findings show the RPN values for each marketing activity. For promotion strategies, the risk of outdated social media content (R8) has a weight score of 0.510, with the priority alternative strategy being the use of content editing technology, scoring 0.594. This strategy involves using editing applications to attract attention on social media. For place strategy, the risk of incomplete address information (R6) has a weight score of 0.237, with the priority alternative strategy being mentoring employees, scoring 0.528. This involves guiding employees to always provide complete address details to customers unfamiliar with the business location. For pricing strategy, the risk of competitors lowering prices (R5) has a weight score of 0.182, with the priority alternative strategy being the implementation of a Standard Operating Procedure (SOP) for market research, scoring 0.633. This strategy seeks to minimize human error during the frying process, ensuring employees are knowledgeable about maintaining product quality to prevent mold growth.